2023
DOI: 10.1007/s11468-022-01761-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of Coronavirus Detection Using Photonic Crystal Fibre–Based SPR Sensor

Abstract: Coronavirus disease (COVID-19) is a worldwide health emergency caused by the coronavirus 2 (severe acute respiratory illness) (SARS-CoV-2). COVID-19 has a wide range of symptoms, making a definitive diagnosis difficult. The shortage of equipment for testing technology COVID-19 has resulted in long queues for COVID-19 testing, which is a major problem. COVID-19 testing is currently performed using sluggish and costly technology like single-photon emission computed tomography (SPECT), computed tomography (CT), p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recently, a study by Gupta revealed that a PCF-based multilayered SPR sensor can detect COVID-19. 37 Trzaskowski et al used an SPR detection system to effectively detect anti-SARS-CoV-2 with an LOD of 40 ng mL À1 . 38 Fan et al used an SPR biosensor based on a dual signal amplification strategy to efficiently detect the SARS-CoV-2 N protein for 15 min with an LOD of 83 pg mL À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study by Gupta revealed that a PCF-based multilayered SPR sensor can detect COVID-19. 37 Trzaskowski et al used an SPR detection system to effectively detect anti-SARS-CoV-2 with an LOD of 40 ng mL À1 . 38 Fan et al used an SPR biosensor based on a dual signal amplification strategy to efficiently detect the SARS-CoV-2 N protein for 15 min with an LOD of 83 pg mL À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Then the electrons propagate parallel to the surface and produce energetic plasmon electrons through non-radiative excitation [ 2 , 3 ]. When the SPR effect occurs, a tiny deviation in the analyte refractive index (RI) or other variables of the propagation medium and multi-physics system will change the phase-matching condition and further hinders the SPR excitation [ 4 , 5 ], making it play a dominant role in real-time interaction sensing of biomolecular binding events [ 6 ] and feasible for analyte measurements and multi-physics system sensing, especially medical reagent testing services in the global public health crisis [ 7 , 8 , 9 ]. In recent years, with extensive research on photonic crystal fibres (PCFs) [ 10 ], findings have concluded that PCF is an excellent environment for the SPR effect to be excited because of its distinctive optical properties and a designable structure with different geometries and materials to choose from [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the electrons propagate parallel to the surface and produce energetic plasmon electrons through non-radiative excitation [2,3]. When the effect happens, a minuscule change in the reflective index (RI) or other variables of the background medium or multi-scale system will alter the phasematching condition and further hinder the occurrence of the excitation of the SPR effect, which makes it feasible for the measurement of analyte RI or other objects in the field of sensing, especially medical testing services in the context of the coronavirus disease [4][5][6]. In recent years, with extensive studies and applications on photonic crystal fibers (PCFs) [7], the findings have concluded that PCFs are a satisfactory environment for the SPR effect to be excited due to its distinctive optical properties and a designable structure with a variety of geometrical topologies and plasmonic materials to choose from [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%